The effect of final dissertation defence language, native vs. non-native, in the psychophysiological stress response of university students (2020)
The objective of this study was to analyse the effect of final dissertation defense language in the autonomic stress response and cortical arousal of Physiotherapy students. We analysed in 110 students divided in 2 groups: native language (83) and non-native language (27), the autonomic stress response in four different moments of the dissertation defence; the cortical arousal and subjective perception of distress before and after the dissertation; and academic performance perception of students and the real performance obtained. Results showed a high sympathetic modulation at the beginning of the evaluation, which was maintained until the end of the evaluation in both groups. In addition, no decrease in cortical activity was found, possibly due to the short time of exposure to the stressful event. The final dissertation defense of Physiotherapy students produces an anticipatory anxiety response and a maintained high sympathetic nervous system activation during the defense, not negatively affecting cortical arousal, regardless of defending in native or non-native language